2015
DOI: 10.1021/acs.cgd.5b01436
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Polymers with High Energy Density: An Emerging Class of Explosives

Abstract: Coordination polymers (CPs) have recently emerged as a promising class of high energy materials useful for the synthesis of tailored energetic materials. CPs have shown potential to improve energetic performance relative to conventional organic energetic materials with regard to density, oxygen balance, sensitivity, and heat of detonation. Thus far, a variety of energetic linkers have been applied, and success has been achieved across a number of structure classes including nitrogen-rich heterocycles and azide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 71 publications
0
98
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18] As an ew access to IHEs, energetic coordination polymers (ECPs) [19][20][21][22][23][24][25][26][27][28][29][30][31][32] are emerging with both excellent safety and high energy,ast heir specific composition(organicsand inorganics) and various dimensionalities (1D, 2D, and3 D) give strong structuralr einforcements and extensive coordination networks, in whichs horter covalentc oordination bonds will lead to higherd ensity ands tability. [33][34][35][36] Inspired by this, many ECPs have been synthesized and characterizedd uring last decades ince the first one was achievedb yH ope-Weeks and co-workers. [37,38] However,i deal insensitive high-energetic coordination polymers (IH-ECPs) conforming to the concept of IHEs with outstanding insensitivity (IS > 40 J, FS > 360 N) and detonation velocity( D > 9kms À1 )a re rare in the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] As an ew access to IHEs, energetic coordination polymers (ECPs) [19][20][21][22][23][24][25][26][27][28][29][30][31][32] are emerging with both excellent safety and high energy,ast heir specific composition(organicsand inorganics) and various dimensionalities (1D, 2D, and3 D) give strong structuralr einforcements and extensive coordination networks, in whichs horter covalentc oordination bonds will lead to higherd ensity ands tability. [33][34][35][36] Inspired by this, many ECPs have been synthesized and characterizedd uring last decades ince the first one was achievedb yH ope-Weeks and co-workers. [37,38] However,i deal insensitive high-energetic coordination polymers (IH-ECPs) conforming to the concept of IHEs with outstanding insensitivity (IS > 40 J, FS > 360 N) and detonation velocity( D > 9kms À1 )a re rare in the published literature.…”
Section: Introductionmentioning
confidence: 99%
“…Matzger et al. have also identified that the hydrogen‐bond functionality acts as an important interaction in peroxides and energetic materials . The principal binding forces in these crystals are hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogenrich compounds constitute a large family of interesting compounds, which are certainly no less active than the traditional CHON energetic materials [4,5]. It is worth noting that they have boosted the development of energetic salts [6][7][8], energetic coordination polymers (CPs, also defined as energetic metal organic frameworks (MOFs) in some cases) [9][10][11], and energetic co-crystals [12,13], and thus significantly expanded the range of energetic materials.…”
Section: Introductionmentioning
confidence: 99%